Answer:
[tex]h(t) = 0.75t^2 + 4t + 12[/tex]
Step-by-step explanation:
The equation given calculates the derivative of the height in relation to the time, that is, the rate of change of the height. To find the equation for the height, we need to integrate this equation:
[tex]dh/dt = 1.5t + 4[/tex]
Multiplying both sides by 'dt', we have:
[tex]dh = (1.5t + 4)dt[/tex]
Using the integral in both sides:
[tex]\int dh = \int (1.5t + 4) dt[/tex]
[tex]h = 0.75t^2 + 4t + h(0)[/tex]
[tex]h = 0.75t^2 + 4t + 12[/tex]
So the height after t years is represented by this equation:
[tex]h(t) = 0.75t^2 + 4t + 12[/tex]